Crooked little vein - Ellis, Warren (Harper Perennial, 2008)
Burned-out private detective Michael McGill is covertly hired to locate an alternative fallback version of the Constitution, an assignment that is complicated by a polyamorous sidekick and a haphazard introduction to an unorthodox use of warm saltwater.